An Assessment on Leadership Training and Development Practices: The Case of Ethiopian Federal Police Commission - Kindu, Melesse (African Journal of Leadership and Development, 2023)
This study tried to assess the leadership training and development practices in Ethiopian Federal Police Commission. To achieve the intended objectives of the study, explanatory concurrent research design with mixed research approach were employed. The primary data were gathered through questionnaire, interview, and document analysis. The quantitative data were analyzed by using descriptive statistics (mean, standard deviation and frequency distribution) and inferential statistics (correlation), while the qualitative data were analyzed by using thematic content analysis technique. The study revealed that at the institution in question, training and development activities are carried out for leadership development purposes. The types of training mostly rendered for police leaders was short-leadership courses, as well extended leadership opportunities were sometimes offered to senior leaders. The status of current practices on leadership training and development were inadequate. As compared to the sample mean for training and development strategies, the study indicated that experiences and learning strategies had the highest mean value. The strategies for leadership training and development are not integrated and well-performed. Those practices of leadership were restrained by various factors like personal and organizational. The study also pointed out that the Police Commission provided inconsistent leadership training and development philosophy that did not properly support and promote leadership development. This led to poor performance on the leaders in training and the organization as well. Therefore, the Federal Police Commission should improve and develop leaders through an integrated leadership training scheme and development strategies.